Metadata cataloging: business metadata description based on the bibliographic principles and objectives - Brandt, Mariana Baptista [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio; Amorim da Costa Santos, Placida Leopoldina Ventura [UNESP]; Zafalon, Zaira Regina (Univ Federal Minas Gerais, Escola Biblioteconomia, 2019)
The present article analyses the bibliographic principles and objectives postulated throughout the years in the discussions about cataloging seen from the business metadata management. It discusses the definitions of metadata and business metadata and approaches the activities of bibliographic description and metadata management. In the bibliographic objectives and principles guidelines are found for the activity of description, which is fundamental for the business metadata management.
Keywords: Business metadata; Metadata management; Cataloging; Bibliographic principles; Bibliographic objectives